Three-Dimensional Visualization of the Podocyte Actin Network Using Integrated Membrane Extraction, Electron Microscopy, and Machine Learning. Issue 1 (January 2022) - Qu, Chengqing; Roth, Robyn; Puapatanakul, Pongpratch; Loitman, Charles; Hammad, Dina; Genin, Guy M.; Miner, Jeffrey H.; Suleiman, Hani Y.
Significance Statement: Podocytes have interdigitated foot processes with intricate three-dimensional structures that are crucial for glomerular filtration. Electron microscopy shows podocytes' complex morphology, but direct visualization of their cytoskeleton and definitive identification of the proteins that comprise the cytoskeletal structures have remained elusive. The authors describe a novel technique that reveals the three-dimensional organization of the podocyte cytoskeleton, finding that actin cables inside foot processes are connected directly to slit diaphragms, to form a continuous mesh-like sheet covering the glomerular basement membrane. Their findings also reveal these actin cables to be part of an extensive, contiguous actin network surrounding the major processes and the podocyte cell body. Applying this technique may help elucidate the mechanobiologic mechanisms regulating podocyte architecture and reveal the ultrastructural changes in the actin network on podocyte injury. Visual Abstract: Abstract : Background: Actin stress fibers are abundant in cultured cells, but little is known about them in vivo . In podocytes, much evidence suggests that mechanobiologic mechanisms underlie podocyte shape and adhesion in health and in injury, with structural changes to actin stress fibers potentially responsible for pathologic changes to cell morphology. However, this hypothesis is difficult to rigorously test in vivo due to challenges with visualization. A technology to image the actin cytoskeleton at high resolution is needed to better understand the role of structures such as actin stress fibers in podocytes. Methods: We developed the first visualization technique capable of resolving the three-dimensional cytoskeletal network in mouse podocytes in detail, while definitively identifying the proteins that comprise this network. This technique integrates membrane extraction, focused ion-beam scanning electron microscopy, and machine learning image segmentation. Results: Using isolated mouse glomeruli from healthy animals, we observed actin cables and intermediate filaments linking the interdigitated podocyte foot processes to newly described contractile actin structures, located at the periphery of the podocyte cell body. Actin cables within foot processes formed a continuous, mesh-like, electron-dense sheet that incorporated the slit diaphragms. Conclusions: Our new technique revealed, for the first time, the detailed three-dimensional organization of actin networks in healthy podocytes. In addition to being consistent with the gel compression hypothesis, which posits that foot processes connected by slit diaphragms act together to counterbalance the hydrodynamic forces across the glomerular filtration barrier, our data provide insight into how podocytes respond to mechanical cues from their surrounding environment.